Journeys for Freedom: A New Look at America's Story - Buckley, Susan and Leacock, Elspeth (Houghton Mifflin Company, 2006)
Each dynamic spread in Journeys for Freedom maps a factual account of real people pursuing freedom$1 (Band creating America$1 (Bs story. Continuing their innovative storytelling approach, Susan Buckley and Elspeth Leacock invite you to trace the travelers across space and time as they forge a future for themselves and for our nation.s
Keywords: Biography & Autobiography; Historical; Juvenile Nonfiction